A qualitative exploration of race‐based differences in social support needs of diverse women with breast cancer on adjuvant therapy. Issue 3 (5th February 2019) - Paladino, Andrew J.; Anderson, Janeane N.; Graff, J. Carolyn; Krukowski, Rebecca A.; Blue, Ryan; Jones, Tameka N.; Buzaglo, Joanne; Kocak, Mehmet; Vidal, Gregory A.; Graetz, Ilana
Abstract: Objective: Social support is a critical component of breast cancer care and is associated with clinical and quality of life outcomes. Significant health disparities exist between Black and White women with breast cancer. Our study used qualitative methods to explore the social support needs of Black and White women with hormone receptor‐positive breast cancer on adjuvant endocrine therapy (AET). Methods: We conducted four focus group (FG) interviews (N = 28), stratified by race (ie, Black and White) and time on AET. FGs were audiotaped, transcribed, and analyzed according to conventions of thematic analysis. Results: Participants noted the importance of having their informational and emotional social support needs met by friends and family members. White participants reported support provided by others with breast cancer was crucial; Black women did not discuss other survivors as part of their networks. Notably, both White and Black participants used the FG environment to provide experiential social support to each other. Conclusions: White participants noted that having other breast cancer survivors in their support network was essential for meeting their social support needs. However, Black participants did not reference other breast cancer survivors as part of their networks. Cancer centers should consider reviewing patients' access to experiential support and facilitate opportunities to connect women in the adjuvant phase.